UTILIZATION OF THE VISCERAL ORGANSOF CATFISH (Pangasius hypoptalmus) ADDED TO BANANA PEEL (Musa acuminata balbisiana) TO PRODUCELIQUID ORGANIC FERTILIZER - Fryathama, Ilham; Sukmiwati, Mery; ', Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study aimed to obtain liquid organic fertilizer produced from the visceral organs of catfish added to banana skin for enriching the macro elements N, P, and K.The method used in this study was the experimental. Parameters used were the value of pH, nitrogen, phosphorus and potassium. The experimentwas composed as completely randomized design (CRD), and the treatment was addition of banana peel which varied into 4 different amoun, namely: without the banana peel (K0), banana peel 100 g (K1) banana peel200 g (K2), banana peel 300 g (K3), and then fermented for 13 days. The results showed that the bestliquid organic fertilizer was produced by the treatment of addition of banana peels 300 g (K3). The characteristics of the fertilizer were pH value of 6.97, the content of nitrogen was 3.02%, phosphoruswas 1.55% and potassium was 3.15%. The pH value, the content of nitrogen and potassium were met to the standard, while the content of phosphoruswas not met the standards of Agriculture No. 70 Permenten SR.140 / 10/2011.Keywords:Produceliquid organic fertilizer, banana speeel, the value of n, p, k